Управління асортиментом та просуванням товарів в умовах ринкових трансформацій - Білоцерківський, Олександр Борисович; Гудименко, Вячеслав Павлович; Момотков, Ігор Сергійович (Видавничий дім "Гельветика", 2025)
Стаття присвячена вивченню актуальних питань управління асортиментом та просуванню товарів з урахуванням впливу на них процесів ринкової трансформації економіки. Встановлено, що управління асортиментом та просуванням товарів відіграє важливу роль в забезпеченні конкурентоспроможності підприємства. Доведено, що заходи оптимізації структури асортименту та просування товарів повинні бути логічно та органічно пов’язані між собою. Запропоновано підхід до управління асортиментом та просуванням товарів на основі двох-факторного АВС-аналізу з візуалізацією результатів у вигляді матриці. Обґрунтовано, що розроблений підхід дозволяє визначити положення кожного товару серед усіх товарів асортименту підприємства, що стає основою для визначення завдань управління асортиментом та просуванням даних товарів, а також вибору характеру заходів просування, що мають розроблятися та впроваджуватися на підприємстві. Processes associated with market transformation have led to fundamental changes in the economy, related to the reform of property relations, the development of entrepreneurship and the formation of competitive relations. In such conditions, the question of ensuring the competitiveness of enterprises arises, one of the ways of which is to improve the management of the assortment and promotion of goods. Purpose. The article is devoted to the study of topical issues of assortment management and product promotion in modern conditions, which are characterized by the deepening of market transformation processes in the economy, and the development of an approach to assortment management and product promotion based on a two-factor ABC analysis of the assortment. Methods. Systematization methods were used to generalize the views of scientists on issues of assortment policy and product promotion, the method of classifying products based on two-factor ABC analysis of the assortment – to divide the assortment of products into categories, the matrix method – to visualize its results. In order to determine the tasks in the field of assortment management and product promotion, it was proposed to apply a situational approach. Results. It is established that the management of the assortment and promotion of goods plays an important role in ensuring the competitiveness of the enterprise. It is proved that measures to optimize the structure of the assortment and promotion of goods should be logically and organically interconnected. An approach to the management of the assortment and promotion of goods based on two-factor ABC analysis with visualization of the results in the form of a matrix is proposed. The zoning of the matrix of the two-factor ABC analysis of the assortment is considered and the tasks of managing the assortment and promotion of goods depending on the sector of the matrix are identified. Conclusion. The developed approach to managing the assortment and promotion of goods can be used to categorize the company’s goods. Displaying its results in the form of a matrix allows you to clearly display the position of each product or product group in the assortment, which becomes the basis for determining the tasks of managing the assortment and promotion.
Management of the assortment and promotion of goods in the conditions of market transformations
Keywords: ринкова трансформація; конкурентоспроможність; управління; асортиментна політика; АВС-аналіз; просування товарів; market transformation; competitiveness; management; assortment policy; ABC analysis; product promotion